(untitled) (Tzintzun, Revista de Estudios Históricos, 2021)
The complexity of the phenomenon of servitude in Colonial Charcas (Bolivia) reveals that children of different origins were subject to coercive conditions similar to those of legal slavery. This analysis shows the working reality of Afrodescendantsand indigenous people in the jurisdiction. It points out to the keys of the mentality and daily behaviorof society in its dynamics of use-abuse of available child labor. The proposal contributes to the study of the relationships of free and unfree labor dependency at the intersection between origin, sex and age of these children.